ANALISIS DAMPAK IMPLEMENTASI SISTEM INFORMASI DESA (SID) TERHADAP TATA KELOLA PEMERINTAHAN - Ucu Nugraha; Yani Iriani; Riki Ridwan Margana (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
Currently, rural areas are a sector that the government pays attention to, as is the case in West Java province, in 2021 disbursing Bankeu of approximately Rp. 130 million per village for 5,312 villages in West Java. This is very risky for fraud to occur, so there is a need for openness in financial management, one of which is the delivery of up to date information through online media in the form of a Village Information System. Various information owned by the village can be easily and quickly conveyed, whether it is about development, MSMEs, PKK activities, Youth Organizations, and so on. The results of SID implementation are manifested in the form of a web that can provide services and open village information to all village residents or stakeholders, and as an effort to support the welfare of village communities.